TAPPING INTO THE WORLD HALAL MARKET: SOME DISCUSSIONS ON MALAYSIAN LAWS AND STANDARDS - Zakaria, Zalina (Jurnal Syariah, 2008)
Recently, the HDC or Halal Development Corporation took over the administration of halal from JAKIM (Department of Islamic Development of Malaysia) to establish a specific body that is fully in charge of the halal administration. This appears to be one of the initiatives the government has implemented to raise Malaysia’s standing as a major player in the world halal industry. In its implementation there must also be laws imposing criminal liability on the violation of halal, as well as particular standards for its achievement. This article discusses the laws that impose criminal liability as well as the Malaysian Halal Standard to determine whether Malaysia can position itself as the ‘model’ country for taking charge of halal matters globally.